Challenges to implementing integrated mathematics learning with Islamic values in Islamic schools in East Java - Rahmah, Nur Lailatul; Hasyim, A. Wahid; Masamah, Ulfa (Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study seeks to examine the challenges encountered by teachers in implementing mathematics instruction integrated with Islamic values in Islamic schools. A descriptive qualitative approach was employed, involving three mathematics teachers from three Islamic schools in East Java, selected through purposive sampling. Data were obtained through semi-structured interviews and document analysis of Lesson Plans (RPP), and subsequently analyzed using the Miles and Huberman model. The validity of the data was ensured through source triangulation. The findings revealed several challenges, including limited knowledge regarding the integration of Islamic values, insufficient professional training, the prevailing perception of mathematics as a value-neutral discipline, and low student interest in mathematics. These challenges contributed to the less-than-optimal attainment of students’ religiosity, motivation, and academic performance. Consequently, it is recommended that schools provide systematic training and integrative modules to enhance teachers’ competence in applying Islamic value-based mathematics instruction